Let´s learn english, travel around the world and greet our family - Riera Trelles, Virgilio; Andrade Arévalo, Vinicio
The students of the Eighth courses of the Benigno Malo High School whose parents have migrated, whether father, mother or both, have learning problems in all the subjects, specially in English during the school year 2004 - 2005, even though, according to some interviews, they also have some expectations to travel to meet their parents in the USA. For this situation, we propose to reform the English curriculum for the eighth courses in the Benigno Malo High School in order to get a real significant learning with this group of students, who are highly representative, both in qualitative as well as in quantitative terms This proposal suggests a variety of new curricular and extracurricular activities focused to motivate and awaken the interest for learning English which somehow will be useful for the students when their migration dream comes true